Analisis Pengaruh Praktek dan Integrasi Rantai Pasok Terhadap Kinerja Operasional UKM Agroindustri Di Kota Malang - Tirta Yoga; Djoko Koestiono; Agustina Shinta (Kadiri University, 2022)
This study, which evaluates the relationship between operational performance, supply chain management, and supply chain integration, covers several small and medium enterprises (SMEs) in Malang. In accordance with the main objective, it will be determined whether the supply chain management method affects operational performance and whether supply chain management affects operational performance. A total of 100 questionnaires were delivered to owners or managers of small and medium-sized agroindustry companies in Malang City. A minimum of one year of supply chain management (SCM) expertise was required for small and medium-scale food and beverage agroindustry in Malang. Analytically, multiple regression was chosen to test the tested hypothesis. There was a positive correlation between supply chain management practices and operational performance efficiency. However, a negative correlation was found between supply chain integration and operational performance, while a positive correlation was found in another study conducted in Malang City, Indonesia. According to this study, there was a relationship between supply chain management methods and operational effectiveness in food and beverage agroindustry SMEs. Studi yang mengkaji hubungan kinerja operasional dengan manajemen rantai pasok dan integrasi rantai pasok ini melibatkan banyak perusahaan kecil dan menengah (UKM) di Malang. Sesuai dengan tujuan utama penelitian ini, akan ditentukan apakah pendekatan manajemen rantai pasokan mempengaruhi kinerja operasional atau tidak, dan apakah manajemen rantai pasok mempengaruhi kinerja operasional. Sebanyak 100 kuesioner dikirimkan kepada pemilik atau pengelola perusahaan agroindustri kecil dan menengah di Kota Malang. Minimal satu tahun Keahlian dalam supply chain management (SCM) diperlukan untuk agroindustri makanan dan minuman skala kecil dan menengah di Malang. Regresi berganda dilakukan secara analitik untuk mengevaluasi hipotesis yang diuji. Sementara metode manajemen rantai pasokan dan efisiensi kinerja operasional berkorelasi positif, integrasi rantai pasokan dan kinerja operasional berkorelasi negatif dan korelasi positif ditemukan antara keduanya dalam studi yang dilakukan di Kota Malang, Indonesia. Berdasarkan penelitian ini, terdapat hubungan antara pendekatan manajemen rantai pasokan dengan keberhasilan operasional pada UKM agroindustri makanan dan minuman.